Everyday survival why smart people do stupid things - Gonzales, Laurence, 1947-; Collins, Kevin T.; BBC Audio (United States : BBC Audio, 2008)
aurence Gonzales turns his talent to the topic of how we can best use the lessons of our evolutionary history to overcome the hazards of everyday life. He finds that natural laws profoundly affect our actions, and he reveals the hidden causes and costs of our behavior, whether as individuals or as a species whose decisions may be leading to darker times
The untied knot -- Training scars -- When modern people face ancient hazards -- The sign of the hand -- Groupness -- The corporate emotional system -- The teachings of Don Juan -- Pleonexia --'The earth is rotting' -- The cosmic cheat sheet -- The 10,000-watt lightbulb -- The inside-outside problem -- Why we care -- The climax shape -- The guest star -- Land's end
Title from container
Narrated by Kevin T. Collins
Keywords: Intellect; Stupidity; Life skills; Errors